Molecular characterization of Salt and Drought Tolerant Mutant and Parental Plants by Using RAPD - Gadakh, S. S.; Patel, D. U.; Singh, Diwakar (International Journal of Bio-resource and Stress Management, 2017)
Present experiments were carried out in 2011 to 2014 at tissue culture laboratory of Main Sugarcane Research Station and Department of Plant Molecular Biology and Biotechnology, Navsari Agricultural University, Navsari to evaluate variability at molecular level between parent and salt and drought tolerant mutant developed by application of selection pressure in tissue culture. Ethyl Methane Sulphonate EMS (0.5% for 2 hours) treated embryogenic calli of sugarcane (Saccharum spp. Complex,cv. Co 99004). Calli were cultured on a selective medium containing NaCl (100 mM) and PEG (2%) for development of salt and drought tolerant plants separately, primer OPK-4 produced maximum 12 bands out of which one was polymorphic. The primer OPK-20 produced 3 monomorphic bands out of total 9 bands. Primer OPK-10 produced maximum polymorphism (100%) followed by primer OPK-04 (91.67%), OPK-15 (88.89%) and OPL-03 (88.89%). Line 8 had showed maximum genetic variation to the parental plant (0.543) followed by line 10 (0.556) and line 2 (0.565). The regenerants of Co 99004 were divided into two clusters, which placed lines 1, 2, 3, 4, 5, 6, 7, 9 and control into first cluster whereas, line 8 and 10 into second cluster. The dendrogram also divided maximum salt tolerant and drought tolerant lines into two clusters suggesting that salt regenerants completely different from drought tolerant lines. Maximum salt and drought tolerant lines placed away from the control supporting the polymorphism revealed by the RAPD profile.